Tecnología de información: ¿Herramienta potenciadora para gestionar el capital intelectual? : Information technology: ¿Potential tool for managing intellectual capital? - Briñez Rincón, Moisés Eduardo (Revista de Ciencias Sociales, 2021)
The current business landscape is characterized by being complex, dynamic and, above all, highly competitive. The dynamics of innovation established the need to implement technologies aimed at the development of human talent, strengthening its structure and consolidating strategic relationships. The objective of this research is to analyze information technologies as a tool for the management of intellectual capital in construction companies. The methodological orientation is inserted in the quantitative positivist epistemological approach, of an explanatory type with an experimental design, the population is made up of all the companies in the construction sector of the State of Zulia-Venezuela; The information was collected through a questionnaire of 78 questions, with a reliability of 0.896, obtained by means of Cronbach’s alpha coefficient. The results show that construction companies have information technology components; however, it does not use its applications strategically, but rather, focusing its usefulness on routine operations. Regarding intellectual capital, three elements were identified: Human, structural and relational, the latter presenting great challenges in the consolidation of relationships with key agents such as customers, suppliers and competitors. In conclusion, information technology contributes significantly to the management of intellectual capital.